Exploring the Pattern between Education Attendance and Digital Development of Countries - Oliveira, Tiago (2018)
Oliveira, T., Bacao, F., & Cruz-Jesus, F. (2014). Exploring the Pattern between Education Attendance and Digital Development of Countries. In CENTERIS 2014 - Conference on ENTERprise Information Systems / ProjMAN 2014 - International Conference on Project MANagement / HCIST 2014 - International Conference on Health and Social Care Information Systems and Technologies (Vol. 16, pp. 452-458). (Procedia Technology; Vol. 16). DOI: 10.1016/j.protcy.2014.10.112